Identifying factors for promoting evidence-based policymaking in Japan with the perspective of policymakers, researchers and knowledge brokers: a semistructured interview - Yuko Arimura; Yuko Yanagawa; Shota Kiuchi; Haruka Matsuyama; Hinata Uehata; Maiko Suto; Hisaya Tomori; Kenji Takehara; Sonoko Sensaki (Health Research Policy and Systems)
Abstract Background The promotion of evidence-based policymaking (EBPM) is increasingly recognized globally for its potential to maximize health outcomes by efficiently utilizing finite resources and focusing on evidence. Although previous literature has identified some facilitators and barriers to promoting EBPM, these are mainly produced in Western countries, with no comparable research conducted yet in Japan. In recent years, knowledge brokers (KBs) have been focusing on the potential to facilitate EBPM. However, previous studies have targeted policymakers and researchers. This study explores the factors promoting EBPM in Japan by integrating the perspectives of policymakers, researchers and KBs. Methods Semistructured interviews were conducted with 15 informants, 5 from each stakeholder, including policymakers, researchers and KBs. The data were analysed using an inductive thematic approach. Since this study aimed to identify factors considered necessary by multiple individuals for promoting EBPM rather than extracting atypical opinions, subcategories were defined as those with at least two speakers. Results A total of 15 interviewees (5 from each of the three stakeholders) participated. We identified five categories and 25 subcategories. The identified categories included cooperative engagement between government and external organizations, policy methods and mechanisms, governmental structure and environment, academic environment and development structure of KBs. The extracted subcategories were generating flexible evidence by researchers meeting the policy needs and creating platforms for active exchange of opinions and relationship-building across organizational boundaries. Conclusions Most factors identified in previous studies were observed in the Japanese context. Thus, we recommend that Japan implement interventions already established abroad, as they can significantly contribute to the advancement of EBPM. In addition, by incorporating the perspectives of KBs alongside policymakers and researchers, this study identified factors not addressed in prior research. To further support EBPM advancement, future studies should identify the competencies required for KBs and explore effective strategies for their development.